Communicating Resistance: A Narrative Analysis of Women’s Struggle Against Tyranny - Alensky Perlika; Sukmawati, Lilis (Institut Agama Islam Negeri Kendari, 2025)
Women's resistance against the authoritarianism of the New Order is the socio-political context of Indonesia during the leadership of President Soeharto. In the book